Stereoselective [2+2]-Cycloadditions of chiral allenic ketones and alkenes: Applications towards the synthesis of benzocyclobutenes and endiandric acids. (10th September 2022) - Guo, Renyu; Witherspoon, Brittany P.; Brown, M. Kevin
Abstract: Cyclobutanes are important motifs that have found utility in many contexts. Prior work has demonstrated an enantioselective isomerization/stereoselective [2 + 2] as a means to access bicyclo [4.2.0]octanes. Herein, the utility of this method is demonstrated towards the synthesis of benzocyclobutenes and a key intermediate towards the endiandric acids. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Image 1